2008
DOI: 10.1073/pnas.0712391105
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of IL-32 in myelodysplastic syndrome and chronic myelomonocytic leukemia modulates apoptosis and impairs NK function

Abstract: TNF␣ levels are elevated in the marrows of patients with myelodysplastic syndrome (MDS) and are associated with high rates of apoptosis, which contributes to hematopoietic failure. We observed that exposure of human marrow stroma cell lines HS5 and HS27a to TNF␣ increases levels of IL-32 mRNA. IL-32, in turn, induces TNF␣. Marrow stroma from patients with MDS expressed 14-to 17-fold higher levels of IL-32 mRNA than healthy controls. In contrast, cells from patients with chronic myelomonocytic leukemia (CMML) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(111 citation statements)
references
References 35 publications
2
107
0
2
Order By: Relevance
“…Indeed, the control of NK cell activation and inhibition by and following IL-15 is critical. The absence of IL-15 or overexpression of IL-32a during infection or cancer might lead to progression or persistence of the disease due to the lack of NK cell killing (54)(55)(56). In contrast, an overexpression of IL-15 without proper regulation could cause autoimmunity (57) or even induce leukemia through DNA hypermethylation and chromosome instability (52).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the control of NK cell activation and inhibition by and following IL-15 is critical. The absence of IL-15 or overexpression of IL-32a during infection or cancer might lead to progression or persistence of the disease due to the lack of NK cell killing (54)(55)(56). In contrast, an overexpression of IL-15 without proper regulation could cause autoimmunity (57) or even induce leukemia through DNA hypermethylation and chromosome instability (52).…”
Section: Discussionmentioning
confidence: 99%
“…IL-32 has also been shown to induce apoptosis in other experimental conditions. For example, Marcondes et al (46) showed that KG1a leukemic cells underwent apoptosis when cocultured with HS5 stromal cells and that apoptosis was due to IL-32 produced by the stromal cells. The abundant expression of IL-32 in lungs of COPD patients (66) may indirectly indicate increased apoptosis because apoptosis is considered to be an important mechanism in the pathogenesis of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Goda et al (51) showed that IL-32 induces apoptosis in T cells. More recently, IL-32 produced by stromal cells induced apoptosis of cocultured leukemic cells (46). Because apoptosis is an important effector mechanism for killing intracellular M. tuberculosis bacteria (62), we measured the effect of exogenous IL-32 on apoptosis of THP-1 cells.…”
Section: Il-32a or Il-32g Induces Macrophage Apoptosis In The Presencmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact function of IL-32 is not clear but it has been implicated in inflammatory disorders such as rheumatoid arthritis (14), Mycobacterium tuberculosis infection (15), and inflammatory bowel disease (16). Recently, there has been a focus on the expression of IL-32 in human malignancies such as stomach cancer (17), lung cancer (18), pancreatic cancer (19), hematopoietic malignancies (20,21), and uterine cervical cancer (22). There are no previous studies about the expression of IL-32 in RCC.…”
Section: Introductionmentioning
confidence: 99%